Lebanon Economic Monitor, Spring 2021 : Lebanon Sinking (to the Top 3) - World Bank (World Bank, Washington, DC, 2021)
The Lebanon financial and economic crisis is likely to rank in the top 10, possibly top three, most severe crises episodes globally since the mid-nineteenth century. This is a conclusion of the Spring 2021 Lebanon economic monitor (LEM) in which the Lebanon crisis is contrasted with the most severe global crises episodes as observed by Reinhart and Rogoff over the 1857-2013 period. The Lebanon economic monitor provides an update on key economic developments and policies over the past six months. Monetary and financial turmoil are driving crisis conditions, more palpably through interactions between the exchange rate, narrow money, and inflation. Real gross domestic product (GDP) growth is estimated to have contracted by 20.3 percent in 2020, on the back of a 6.7 percent contraction in 2019. The deliberate depression has further undermined already weak public services via two effects: (i) it has significantly increased poverty rates expanding the demography that is not able to afford private substitutable (the way citizens had previously adapted to abysmal quality of public services), and are thus more dependent on public services; and (ii) threatens financial viability and basic operability of the sector by raising its costs and lowering its revenues. Lebanon urgently needs to adopt and implement a credible, comprehensive, and coordinated macro-financial stability strategy, within a medium-term macro-fiscal framework. This strategy will be based on: (i) a debt restructuring program that will achieve short-term fiscal space and medium-term debt sustainability; (ii) comprehensively restructuring the financial sector in order to regain solvency of the banking sector; (iii) adopting a new monetary policy framework that will regain confidence and stability in the exchange rate; (iv) a phased fiscal adjustment aimed at regaining confidence in fiscal policy; (v) growth enhancing reforms; and (vi) enhanced social protection.